Chiral analysis of cis-2-methyl-4-propyl-1, 3-oxathiane and identification of cis-2, 4, 4, 6-tetramethyl-1, 3-oxathiane in wine. (30th September 2021) - Wang, Xingchen; Capone, Dimitra L.; Roland, Aurélie; Jeffery, David W.
Highlights: HS-SPME GC–MS method developed for enantiomers of two oxathianes in wine. Strong enantiomeric correlations between 3-SH and its related oxathiane were shown. Chemical formation of oxathiane from 3-SH and acetaldehyde was verified in wine. First identification of cis -2, 4, 4, 6-tetramethyl-1, 3-oxathiane ( cis -TTMO) in wine. Odour threshold of cis -TTMO determined to be 14.9 µg/L in a neutral white wine. Abstract: cis -2-Methyl-4-propyl-1, 3-oxathiane ( cis -2-MPO), arising from 3-sulfanylhexan-1-ol (3-SH) and acetaldehyde, was recently identified in wine, but the enantiomeric distribution was unknown. Such information could reveal influences on wine aroma, given the impact of chirality on odorant molecules. Herein, a stable isotope dilution assay employing headspace solid-phase microextraction with chiral gas chromatography–mass spectrometry was developed, validated, and applied to a selection of wines. Studies with (3 R )-3-SH revealed the elution order of the cis -2-MPO enantiomers and the concentrations of (2 R, 4 S )-2-MPO and (2 S, 4 R )-2-MPO in the studied wines ranged from undetected to 250 ng/L and 303 ng/L, respectively. Strong positive correlations were found between (3 R )-3-SH and (2 S, 4 R )-2-MPO (r = 0.654), and (3 S )-3-SH and (2 R, 4 S )-2-MPO (r = 0.860). Additionally, cis -2, 4, 4, 6-tetramethyl-1, 3-oxathiane, constituted from acetaldehyde and 4-methyl-4-sulfanylpentan-2-ol (4-MSPOH), was identified in wine for the first time. This new 1, 3-oxathiane, which presents a novel fate for 4-MSPOH, was detected in wines as a single enantiomer at up to 28 ng/L.